Leadership Experiences of Internal Medicine Residents: A Needs Assessment for Leadership Curricula - Lyons MD; Oyler J; Iossi K; Merriam S (Dove Medical Press, 2022)
Maureen D Lyons,1 Julie Oyler,2 Katherine Iossi,3 Sarah Merriam4 1Division of General Internal Medicine, Department of Medicine, Washington University School of Medicine, St. Louis, MO, USA; 2Section of General Internal Medicine, Department of Medicine, University of Chicago Pritzker School of Medicine, Chicago, IL, USA; 3Department of Medicine, Portland VA Medical Center, Portland, OR, USA; 4Division of General Internal Medicine, Department of Medicine, VA Pittsburgh Healthcare System and Division of General Internal Medicine, University of Pittsburgh School of Medicine, Pittsburgh, PA, USACorrespondence: Maureen D Lyons, Washington University in St. Louis School of Medicine, 660 S. Euclid Avenue, Campus Box 8121, St. Louis, MO, 63110, USA, Tel +1-314 362 5305, Email lyonsm@wustl.eduPurpose: Leadership development during medical training is critical. Accrediting bodies strongly recommend and residents desire leadership training. However, limited needs assessment data exist regarding trainee perceptions of and experiences with leadership training. Our objective is to describe residents' perceptions of leadership and desires for leadership training with the goal of informing effective curricular development.Patients and Methods: In 2019 a trained qualitative interviewer conducted semi-structured interviews with volunteer second-year categorical internal medicine residents recruited via email across four institutions. Interviews were audio-recorded, transcribed, and inductively coded by two independent coders. After adjudicating discrepancies, coders synthesized codes into broader themes. Final thematic analysis was triangulated with the entire author group.Results: Fourteen residents were interviewed (50% female). Few reported prior leadership training. Thematic analysis yielded six main themes. First, residents perceive "leadership" to be related to formal, assigned, hierarchical roles. Second, residents identify their own leadership primarily in the inpatient clinical setting. Third, residents identify clinical competence, emotional intelligence, and communication as important skills for effective leadership. Fourth, residents struggle to identify where leadership is currently being taught. Fifth, residents desire additional leadership development. Finally, residents prefer well-labeled, interactive methods for leadership development.Conclusion: Although residents desire leadership development, these skills are not often explicitly taught, labeled, or assessed. Curriculum developers may consider explicitly contextualizing leadership training within an "everyday leadership" framework, dovetailing leadership coaching with daily teaching workflow and feedback structures, and implementing faculty development initiatives to allow for appropriate feedback and assessment of these skills.Keywords: graduate medical education, curriculum development, needs assessment, trainee